Edukasi Pendidikan Teman Sebaya Menggunakan Modul Tentang Infeksi Menular Seksual Terhadap Pengetahuan Remaja - Dianna; Diarni, Aha (WOMB Midwifery Journal, 2024)
Adolescence (15-24 years) is a transitional period where the need for attention and protection becomes greater and more specific. Sexually transmitted infections have a significant impact on sexual and reproductive health. Adolescent groups fall into the high-risk category for sexually transmitted infections. Peer counseling has the potential to provide positive reinforcement, where one friend can act as a motivator for another. The aim of this research is to determine the effect of educational interventions by peers using modules on sexually transmitted infections in the prevention of sexually transmitted infections on adolescents' knowledge. This study employs a quasi-experimental design with pre-test and post-test without a control group. The group was provided with educational training using a module on sexually transmitted infections that included: definitions, types, signs and symptoms, modes of transmission, prevention methods for sexually transmitted infections, and how to become a peer counselor. Interventions were conducted twice a week over a period of one week, with pre-tests and post-tests using the same questionnaire. The sample consisted of 42 individuals selected through simple random sampling. A normality test of the data was conducted using the Shapiro-Wilk test, with bivariate analysis using the Wilcoxon test. The results indicated that there was an effect of providing peer education using the sexually transmitted infections module on the knowledge of adolescents.